A Revised Code of Ordinances of the City of Tuscaloosa 149-50, § 330 (1885) - (:unkn) unknown (My University, 1885)
Prohibited use of firearms while fighting in a public place, except for in self defense. On conviction, violator shall pay a fine of no more than $25 and face imprisonment or work for the city for a period not exceeding 30 days.
Keywords: DUELING